Implementasi Islamic Corporate Social Responsibility (CSR) Pada PT. Bumi Lingga Pertiwi di Kabupaten Gresik - Kharisma, Indra; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Implementation of Corporate Social Responsibility (CSR) is used later to improve the image of the company and its business existence. Instead of CSR to empower people its delude people with a profit motive. Islamic CSR is that CSR refers to business practices that have an ethical responsibility Islamically, companies incorporate Islamic norms characterized by sincerity commitment in maintaining the social contract in its business practices in halal lawful. This study aimed to reveal the implementation of Islamic CSR PT. Bumi Lingga Pertiwi Gresik.This study used a qualitative approach with descriptive case study method. The selections of informant are using purposive sampling method. Data collection was conducted by semi-structured interviews and documentation. Analysis of the data using descriptive method.The results of this study indicate that PT. Bumi Lingga Pertiwi has implemented Islamic CSR based on unity, caliphate, justice and broterhood by creating and running a cooperation agreement in accordance with sharia corridor, provide good service to customers, act fairly and avoid discrimination, provide assistance to the poor in the villages around, helping the development of education and worship, as well as participate protecting the environment by way of planting trees together.